Fuchs' Endothelial Corneal Dystrophy in Patients With Myotonic Dystrophy, Type 1 - Winkler, Nelson S.; Milone, Margherita; Martinez-Thompson, Jennifer M.; Raja, Harish; Aleff, Ross A.; Patel, Sanjay V.; Fautsch, Michael P.; Wieben, Eric D.; Baratz, Keith H. (Investigative ophthalmology & visual science, 2018)
RNA toxicity from CTG trinucleotide repeat (TNR) expansion within noncoding DNA of the transcription factor 4 (TCF4) and DM1 protein kinase (DMPK) genes has been described in Fuchs' endothelial corneal dystrophy (FECD) and myotonic dystrophy, type 1 (DM1), respectively. We prospectively evaluated DM1 patients and their families for phenotypic FECD and report the analysis of CTG expansion in the TCF4 gene and DMPK expression in corneal endothelium. FECD grade was evaluated by slit lamp biomicroscopy in 26 participants from 14 families with DM1. CTG TNR length in TCF4 and DMPK was determined by a combination of Gene Scan and Southern blotting of peripheral blood leukocyte DNA. FECD grade was 2 or higher in 5 (36%) of 14 probands, significantly greater than the general population (5%) (P < 0.001). FECD segregated with DM1; six of eight members of the largest family had both FECD and DM1, while the other two family members had neither disease. All DNA samples from 24 subjects, including four FECD-affected probands, were bi-allelic for nonexpanded TNR length in TCF4 (<40 repeats). Considering a 75% prevalence of TCF4 TNR expansion in FECD, the probability of four FECD probands lacking TNR expansion was 0.4%. Neither severity of DM1 nor DMPK TNR length predicted the presence of FECD in DM1 patients. FECD was common in DM1 families, and the diseases cosegregated. TCF4 TNR expansion was lacking in DM1 families. These findings support a hypothesis that DMPK TNR expansion contributes to clinical FECD.